2014
DOI: 10.2217/bmm.14.13
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Analysis and Preterm Infant Health: The Importance of Assay Design in the Search for Novel Biomarkers

Abstract: Preterm infants develop an 'aged' phenotype in comparison with term-born infants, one component of which is adverse metabolic health and, therefore, long-term health follow-up is warranted to identify morbidity. In light of this, the identification and use of biomarkers to aid with prognosis would be a welcome development. Telomeres are repeat sequences at the ends of each chromosome arm known to shorten as a consequence of cellular aging, and in relation to several disease conditions. The hypothesis that expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…51 Benetos et al 52 showed that for a given chronological age, subjects with shorter telomere length are at increased risk for higher pulse wave velocity values.…”
Section: Discussionmentioning
confidence: 99%
“…51 Benetos et al 52 showed that for a given chronological age, subjects with shorter telomere length are at increased risk for higher pulse wave velocity values.…”
Section: Discussionmentioning
confidence: 99%
“…salivary vs. leukocyte telomere length; neonates vs. children vs. adults, TRF vs. PCR-based measurements) many gaps remain in the current literature on the relation between preterm birth and telomere length. This was also emphasized by a recent review on telomere length and preterm birth [ 2 ].…”
Section: Introductionmentioning
confidence: 90%
“…gestational age <37 weeks) [ 1 ]. Next to respiratory morbidity and neurodevelopmental impairment, the ex-preterm infant phenotype is also characterized by adverse metabolic health in later life [ 2 ]: Already at a young adult age, ex-preterms have a higher risk for age-associated diseases, such as cardiovascular disease (CVD) [ 3 7 ] and have increased cardiovascular mortality [ 8 ]. The fetal origin hypothesis [ 9 ] states that this increased risk is programmed during fetal life and that adverse events during pregnancy lead to reprogramming, causing diseases in later adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed to assess telomere length. They include procedures which quantify the mean from total DNA extracted from a population of cells, and those which measure the telomere of individual chromosomes in a cell [ 8 ]. The most established method uses southern blot hybridization analysis of terminal restriction fragments (TRF) to measure the absolute telomere length and the subtelomeric regions.…”
Section: Introductionmentioning
confidence: 99%